Edukasi Masyarakat Tentang Identifikasi Bahaya Pada Proses Pengelasan Besi Untuk Fasilitas Public - Tri Widodo; Ismail Fardiansyah (Pusat Riset dan Inovasi Nasional, 2023)
One of the work activities usually carried out to maintain and repair public facilities in residential communities is the welding process. Of course, correct knowledge is needed regarding a good welding process in order to produce quality welding results so that the object being repaired can last a long time. In the welding process there are several potential dangers which have risks both for the welding worker himself in terms of health and risks for the environment in the form of fire. Education to the public regarding the welding process so that it produces quality results in general includes: ensuring the work area is clean and safe, then the tools and materials used are according to specifications and correct welding techniques are very helpful to the public. Apart from that, recognition of the potential dangers and risks that may arise from the welding process can increase awareness in the community of the importance of implementing occupational health and safety principles.